2019
DOI: 10.18700/jnc.190076
|View full text |Cite
|
Sign up to set email alerts
|

Primary neurocritical care involving therapeutic hypothermia for acute ischemic stroke patients with malignant infarct cores

Abstract: Background: Acute ischemic stroke patients with malignant infarct cores were primarily treated with neurocritical care based on reperfusion and hypothermia. We evaluated the predictors for malignant progression and functional outcomes. Methods: From January 2010 to March 2015 ischemic stroke patients with large vessel occlusion of the anterior circulation with infarct volume >82 mL on baseline diffusion weighted image (DWI) within 6 hours from onset, with National Institutes of Health Stroke Scale ≥15 were inc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
4

Relationship

3
1

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 23 publications
0
3
0
Order By: Relevance
“…For all patients, DHC was usually performed based on clinical signs while managed with neurocritical care. During this period, patients that showed clinical signs such as altered mental status, flexor or extensor motor posturing, pupillary abnormality, repiratory pattern changes, eye movement impairments, or respiratory pattern abnormalities [ 22 ], with evidence of imminent herniation in CT was classified “malignant progressors [ 23 ].” Malignant progression was further divided into early malignant progression if it occurred after CT postprocedure and before CT D1 , and late malignant progression if it occurred after CT D1 . DHC was performed upon consent regardless of age or whether thrombolysis was performed.…”
Section: Methodsmentioning
confidence: 99%
“…For all patients, DHC was usually performed based on clinical signs while managed with neurocritical care. During this period, patients that showed clinical signs such as altered mental status, flexor or extensor motor posturing, pupillary abnormality, repiratory pattern changes, eye movement impairments, or respiratory pattern abnormalities [ 22 ], with evidence of imminent herniation in CT was classified “malignant progressors [ 23 ].” Malignant progression was further divided into early malignant progression if it occurred after CT postprocedure and before CT D1 , and late malignant progression if it occurred after CT D1 . DHC was performed upon consent regardless of age or whether thrombolysis was performed.…”
Section: Methodsmentioning
confidence: 99%
“…TH is a common term for defining intentional cooling in core body temperature and has evolved over decades into a strategy for a more comprehensive control of body temperature. It is now called targeted temperature management (TTM) (11,16,17). Clinical trials have proven that TH is effective in post-cardiac arrest and neonatal hypoxic-ischemic encephalopathy (18)(19)(20).…”
Section: Limitations Of Systemic Therapeutic Hypothermiamentioning
confidence: 99%
“…3). A recent study has shown that neurocritical care treatments including TH are feasible even in patients with a malignant infarct core [39]. Therefore, the strategy reducing reperfusion injury using TH will be another option for vulnerable patients suffering from acute ischemic stroke in the EVT era.…”
Section: Targeted Temperature Management During or After An Endovascumentioning
confidence: 99%